A mathematical model and experimental procedure to analyze the cognitive effects of audio frequency magnetic fields - Navarro, Enrique A.; Navarro-Modesto, Enrique (Frontiers in Human Neuroscience, 2023)
Audio-frequency magnetic fields (20 Hz-20 kHz), are magnetic fields in the Extremely Low Frequency-Very Low Frequency bands (ELF-VLF) that are present near audio equipment and acoustic transducers. These devices transform and operate the electrical signal from the recordings or others devices into acoustic and audio signals. Cognitive influence of sound and noise has been widely studied and recognized since the times of ancient Rome, however the cognitive effects of magnetic fields of these frequencies have not been studied. Due to the extensive use of audio de-vices that use this type of transducers near the temporal-parietal area, we believe that it is of in-terest to study their impact on short-term memory or working memory (WM), also to analyse its potential as they operate as a brain magnetic stimulation. In this work, a mathematical model and an experimental tool are introduced to analise memory performance. The model dissociates the reaction time of a cognitive task. We analyse the model in data from a group of 65 young healthy subjects. WM is assessed in our experimental setup by means of the Sternberg test (ST) so that during the ST a part of them are exposed to an audio frequency magnetic stimulus and the other part receive a sham stimulus. The magnetic stimulus was ~0.1microTesla, which was applied to both sides of the head, frontal cortex near the temporal-parietal area were WM is expected to be located. The ST collects the reaction times when deciding whether an object displayed on the computer screen is one of the objects to be remembered. The results are analyzed within the mathematical model and changes are observed, a deterioration of WM is observed that could affect 32% of its operability.